2004
DOI: 10.1590/s0006-87052004000300003
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do estresse salino sobre a concentração de pigmentos e prolina em folhas de arroz

Abstract: In order to analyse the effect of salt (0, 25, 50, 75 and 100 mM) concentration on chlorophylls, total carotenoids and proline contents, an experiment was carried out in greenhouse conditions with cultivars BRS Bojurú, IAS 12-9 Formosa and BRS Agrisul. Total contents were determined 30 days after soil salinization. The salinity strongly reduced chlorophylls and total carotenoids contents on Agrisul genotype, but pigments were not quite affected on Bojuru and Formosa. Proline contents were ligher in Agrisul th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
3
15
0
10
Order By: Relevance
“…The outcome of increased proline concentration on saline stress has been extensively studied in plants, such as sorghum (De Lacerda et al, 2003), rice (Lima et al, 2004) and canola (Saadia et al, 2012). Specifically on sugar cane, when subjected to 100 mM of NaCl, it is observed the accumulation of this osmolyte in leaves and roots (García and Medina, 2003;Vasantha and Rajlakshmi, 2009;Karpe et al, 2012;Medeiros et al, 2015) which corroborates the present work.…”
Section: Discussionsupporting
confidence: 88%
“…The outcome of increased proline concentration on saline stress has been extensively studied in plants, such as sorghum (De Lacerda et al, 2003), rice (Lima et al, 2004) and canola (Saadia et al, 2012). Specifically on sugar cane, when subjected to 100 mM of NaCl, it is observed the accumulation of this osmolyte in leaves and roots (García and Medina, 2003;Vasantha and Rajlakshmi, 2009;Karpe et al, 2012;Medeiros et al, 2015) which corroborates the present work.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the importance of chlorophyll in the first step of photosynthesis, characterized by the photochemical stage, the high content of salts absorbed by the plants contributed to the increase in the activity of chlorophyllase, an enzyme that degrades chlorophyll (Lima et al, 2004), hampering the formation of these pigments and inhibiting the photosynthetic activity of the plants in general (Munns & Tester, 2008, Taiz & Zeiger, 2013. Comparatively, the effects are similar to those reported by Graciano et al (2011) in peanut plants and by Cavalcante et al (2011) in yellow passion fruit, who observed that irrigation with saline water causes a reduction in the chlorophyll activity of these variables in the respective crops.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to higher contents of chlorophyll a (Figure 2A) in relation to chlorophyll b ( Figure 2B) and, consequently, higher values of the chlorophyll a/b ratio ( Figure 2D). The superiority of the coefficients, according to Lima et al (2004), is due to the higher contents of chlorophyll a in the leaves and to the increase of the efficiency of photosynthetic reactions. This pigment actively participates in the first photochemical process of the photosynthesis, while chlorophyll b is an accessory pigment that has as its main function the absorption of light in the wavelength spectrum not absorbable by chlorophyll a (Taiz & Zeiger, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This amino acid is a biochemical marker of metabolic changes generated by different types of stress conditions. (Lima, 2004) It is synthesized by glutamate, and also by the arginine/ornithine cycle which has the same route as urease. At this phase, it was found that proline synthesis may be favored by low activity of urease.…”
Section: Titanium and The Activity Of Enzymesmentioning
confidence: 99%